Seasonality study of essential oil from leaves of Cymbopogon densiflorus and nanoemulsion development with antioxidant activity - Seibert, Janaína Brandão; Rodrigues, Ivanildes Vasconcelos; Carneiro, Simone Pinto; Amparo, Tatiane Roquete; Lanza, Juliane Sousa; Frézard, Frédéric Jean G.; Souza, Gustavo Henrique Bianco; Santos, Orlando David Henrique dos (Flavour and fragrance journal, 2019)
The development of formulations that maintain the biological and physical chemistry properties of essential oils is an important choice when they are used as an active ingredient. This study aimed to characterize the essential oil from leaves of Cymbopogon densiflorus and evaluate the antioxidant activity of the oil, and to produce a nanoemulsion formulation containing it. The essential oil was obtained by hydrodistillation, and seasonality was analysed every 2 months by gas chromatography–mass spectrometry, showing that more than 90% of the composition was maintained for the whole period and that the major compounds were trans‐p‐menta‐2,8‐dien‐1‐ol, cis‐p‐menta‐2,8‐dien‐1‐ol, trans‐p‐menta‐1(7),8‐dien‐2‐ol, cis‐piperitol, and cis‐p‐menta‐1(7),8‐dien‐2‐ol. Stable nanoemulsions were prepared by phase inversion method encapsulating the essential oil. The antioxidant activity was evaluated by 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH) free radical scavenging and 2,2′‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulphonic acid (ABTS) methods. In the first test, free and nanoemulsified essential oil showed half‐maximal inhibitory concentration (IC50) values equivalent to 14.689 and 3.692 mg mL−1, respectively. In the second test, these values were 0.567 and 0.43 mg mL−1. The development of nanoemulsion‐based essential oil from leaves of C. densiflorus was viable, and the formulated oil was able to reproduce the antioxidant activity at a concentration four times lower than that of the pure essential oil. The development of nanoemulsions based essential oil from leaves of C. densiflorus was viable and able to reproduce the antioxidant activity from a formulated oil concentration until 4 times lower than the pure oil.